The distribution of Babesia odocoilei in Ixodes species ticks in Canada: Implications for one health surveillance - Camille Guillot; Jérôme Pelletier; Cécile Aenishaenslin; Heather Coatsworth; Antonia Dibernardo; Jules K. Koffi; Manisha A. Kulkarni; Jean-Philippe Rocheleau; Christy Wilson; Curtis Russell; Mark P. Nelder; Jacqueline Badcock; et al. (Ticks and Tick-Borne Diseases)
Ixodes scapularis and Ixodes pacificus are vectors of a range of pathogens of public health significance in North America. These ticks transmit pathogens to and from wild animal reservoir host species, but also bite humans and expose them to the pathogens. We describe the geographical and temporal distribution of the pathogen Babesia odocoilei, the causative agent of cervid babesiosis. Ixodes spp. ticks collected through active and passive surveillance were submitted to the National Microbiology Laboratory of the Public Health Agency of Canada for analysis of the presence of B. odocoilei from 2018 to 2021. Generalized linear models were constructed to evaluate the temporal change of B. odocoilei prevalence across Canada. Babesia odocoilei-positive I. scapularis are widespread across south-central and eastern regions of Canada, with an overall prevalence of 12.0 % in both nymphs (CI 95 % : 11.4–12.6) and adults (CI 95 % : 11.9–12.1) collected in passive surveillance and 13.2 % (CI 95 % : 12.9–13.5) and 10.0 % (CI 95 % : 9.8–10.2) in nymphs and adult, respectively, collected in active surveillance. A single I. pacificus tick tested positive in active surveillance out of 29 ticks collected in British Columbia, while no B odocoilei-positive I. scapularis were found in passive surveillance among the 11 adult ticks tested. Although B. odocoilei infection prevalence of adult I. scapularis was significantly higher in 2019 (14.1 %) than in 2018 (7.4 %), it remained stable from 2019 to 2021, suggesting that this pathogen may already be well established in endemic tick populations. The results provided in this article represent, to date, the most comprehensive picture of B. odocoilei distribution and prevalence in ticks in Canada and highlight the interest of maintaining One Health surveillance approaches to give added insight into disease transmission cycles for less well-characterized microorganisms.